The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1088/0031-8949/55/6/018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation concentration on the relaxation phenomena of Co-Zn ferrite

Abstract: The real and imaginary parts of the relative permittivity (ε'r and ε''r) as well as the a.c. resistivity of the mixed ferrite CoxZn1−xFe2O4 (x = 0.1 → 1.0) were measured as a function of temperature and frequency. The calculated values of the activation energy indicate that the conductivity of the system increased with increasing Zn concentration. The Curie temperature of the system as determined from a.c. conductivity measurements agree well with that of the relative permittivity. The calculation of the relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…The variation in dielectric constant (ε I ) with frequency at room temperature for the samples Co (0.5-x) Ni x Zn 0.5 Fe 2 O 4 with x = 0.0, 0.1, 0.2 and 0.3 is shown in Figure 3 The dielectric constant is found to be less than bulk sample for a frequency of 100 KHz at room temperature. The dielectric constant for bulk Co 0.5 Zn 0.5 Fe 2 O 4 as reported by M. A. Ahmed [15] is 105, whereas in the present investigation the dielectric constant for Co 0.5 Zn 0.5 Fe 2 O 4 with particle size 10 nm is calculated as 28. This low dielectric loss is attributed to homogeneity, better symmetry and small grain size when compared with bulk sample [16].…”
Section: Dielectric Constantcontrasting
confidence: 42%
“…The variation in dielectric constant (ε I ) with frequency at room temperature for the samples Co (0.5-x) Ni x Zn 0.5 Fe 2 O 4 with x = 0.0, 0.1, 0.2 and 0.3 is shown in Figure 3 The dielectric constant is found to be less than bulk sample for a frequency of 100 KHz at room temperature. The dielectric constant for bulk Co 0.5 Zn 0.5 Fe 2 O 4 as reported by M. A. Ahmed [15] is 105, whereas in the present investigation the dielectric constant for Co 0.5 Zn 0.5 Fe 2 O 4 with particle size 10 nm is calculated as 28. This low dielectric loss is attributed to homogeneity, better symmetry and small grain size when compared with bulk sample [16].…”
Section: Dielectric Constantcontrasting
confidence: 42%
“…They reported that the samples with smaller grain size show only one semicircle corresponding to grain boundary conduction, while samples of larger size show two semicircles corresponding to both grain and grain boundary conduction mechanisms. Ahmed et al [13] studied the effect of cation concentration on the relaxation phenomena of Co-Zn ferrites. Although the magnetic properties of Mn-Ni-Zn ferrites have been studied [14,15], complex impedance spectroscopy studies of the Mn-Ni-Zn ferrites have not been found extensively in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the samples with smaller grain size show only one semi-circle corresponding to grain boundary conduction, while samples of larger size show two semi-circles corresponding to both grain and grain boundary conduction mechanism. Ahmed et al [15] studied the effect of cation concentration on the relaxation phenomena of Co-Zn ferrites. They reported that the maximum of the relaxation time (), calculated from the Cole-Cole plots corresponds to the critical concentration, x = 0.6.…”
Section: Introductionmentioning
confidence: 99%